Translation Quality of the Book “Poems for You: Hundreds of Modern Chinese Poems” - Amphaithip, Khampha; XUANGAO, Meng; Zhengli, Shang; Khounsavath, Phetsamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of the study was to explore the disparities between the original and translations of "Poetry for You: Hundreds of Contemporary Chinese Poems," and assess the quality of its translation into Lao. It was qualitative research in which the researchers identified words, expressions, and sentences. The study found that the research for inequality between the original and the translation contained 4 cases of expectation, 100 cases of humanist meaning, 30 cases of meaning, The study found that in the study of inequality between the original and the translation, there were 4 discrepancies: expectation cases: 100 cases; humanistic meaning 30 cases; meaning 34 cases; form 11 cases; It also found that there were 6 cases of misspelling. As for the quality assessment of the translation into Lao, it was found that the quality of the translation into Lao was good. It demonstrates the purpose of the author in its entirety and has a variety of translation methods, such as additional translations, cut-word translations, translations using alternate meanings, narrow meanings to wide meanings, and clear meanings as the meaning is hidden so that the content of the chapter has a deeper meaning and the reader can easily understand the meaning of the chapter. The purpose of the study was to explore the disparities between the original and translations of "Poetry for You: Hundreds of Contemporary Chinese Poems," and assess the quality of its translation into Lao. It was qualitative research in which the researchers identified words, expressions, and sentences. The study found that the research for inequality between the original and the translation contained 4 cases of expectation, 100 cases of humanist meaning, 30 cases of meaning, The study found that in the study of inequality between the original and the translation, there were 4 discrepancies: expectation cases: 100 cases; humanistic meaning 30 cases; meaning 34 cases; form 11 cases; It also found that there were 6 cases of misspelling. As for the quality assessment of the translation into Lao, it was found that the quality of the translation into Lao was good. It demonstrates the purpose of the author in its entirety and has a variety of translation methods, such as additional translations, cut-word translations, translations using alternate meanings, narrow meanings to wide meanings, and clear meanings as the meaning is hidden so that the content of the chapter has a deeper meaning and the reader can easily understand the meaning of the chapter.